Korelasi Antara Kedaulatan Allah dengan Penderitaan Orang Percaya - Nurlela Syafrian Oematan; Pujiwati Pujiwati; Jaminter Ompusuggu; Joshua Christian Wenas (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
The sovereignty of God as the core understanding of the true God according to the Bible and the relationship between the concept of God's sovereignty and the suffering experienced by believers in the context of Christian theology. The purpose of this research is to clarify how the concept of God's sovereignty influences perceptions and investigate how views on God's sovereignty and those beliefs provide comfort and meaning in the experience of suffering in daily life. The method used is theological analysis of biblical texts and relevant theological literature with a qualitative approach to explore the meaning and implications of God's sovereignty on the experiences and beliefs of individuals facing suffering. The research findings indicate that the concept of God's sovereignty plays a crucial role, and a correct understanding of God's sovereignty helps believers to uncover, overcome, and respond to suffering by offering a strong foundation of faith and hope in divine comfort through understanding His hidden will and plan in the experience of suffering. The implications of these findings provide deep theological insights and emphasize the importance of strengthening faith and theological reflection in addressing spiritual and emotional challenges of suffering, as well as expanding the church community's understanding of God's sovereignty as a basis for addressing questions about human suffering.